Ultrastructural studies of the termite (Odontotermes obesus)gut microflora and its cellulolytic properties - Paul, J.; Saxena, S.; Varma, A.
The major gut microflora colonizing the hind gut of a higher termite, Odontotermes obesus, included morphologically diverse bacteria, both coccoid and rod-shaped, along with spirochaetes, pseudomonads and actinomycetes. Flagellated protozoa were totally absent. When the gut extract was inoculated on plates containing carboxymethyl cellulose or cellobiose, higher numbers of bacteria grew than on plates without cellulosic sources. The gut homogenate exhibited strong hydrolytic activity when carboxymethyl cellulose, pnitrophenyl-FD-glucoside or xylan were used as substrate, indicating the role of gut microbiota in the process of cellulose and hemicellulose digestion. Activities were highest in the hind gut, and the paunch was probably the major site of polysaccharide digestion in this higher termite. In vitro cultivation of some of the isolates revealed both cellulase and xylanase activities. To our knowledge, this is the first report on ultrastructural studies of the higher termite dontotermes obesus.
Keywords: ELECTRON MICROSCOPY; CELLULOYTIC MICROORGANISMS; TERMITE GUT